ruang topologi - Ilmi Satriani (Jurnal Pustaka Cendekia Pendidikan, 2024)
f separation is an axiom used to classify topological spaces based on their open set distribution. The method used in this study is to combine the premises of the axioms of separation in topological spaces so that a theorem connecting the topological spaces can be obtained. In this study, the relationship between the topological spaces is obtained, that is, every T4 space is a T3 space, every T3 space is a T2 space, every T2 space is a T1 space, but the reverse statement does not apply. It is also obtained that each metric space satisfies all the axioms of separation in the spaces T1, T2, T3, and T4. Discussion about the axioms of separation in topological spaces is still open by comparing the axioms of separation of more complex topological spaces such as Tychonoff spaces and Urysohn spaces.